2022
DOI: 10.3390/ijms23169316
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc in the Treatment of Wilson’s Disease

Abstract: Wilson’s disease (WD) is a hereditary disorder of copper metabolism, producing abnormally high levels of non-ceruloplasmin-bound copper, the determinant of the pathogenic process causing brain and hepatic damage and dysfunction. Although the disease is invariably fatal without medication, it is treatable and many of its adverse effects are reversible. Diagnosis is difficult due to the large range and severity of symptoms. A high index of suspicion is required as patients may have only a few of the many possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 133 publications
0
23
0
2
Order By: Relevance
“…However, the disruption of Cu homeostasis could also lead to the accumulation of reactive oxygen species and proteasome inhibition, causing cellular toxicity [ 39 ]. Abnormal accumulation of Cu was previously reported to be associated with the development of several disease, such as wilson's disease and neuroinflammation [ 40 , 41 ]. Recently, increasing number of studies have revealed that Cu metabolic reprogramming and Cu-dependent cellular process are crucial for cancer development, and it is important to uncover the underlying regulatory mechanisms of Cu in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the disruption of Cu homeostasis could also lead to the accumulation of reactive oxygen species and proteasome inhibition, causing cellular toxicity [ 39 ]. Abnormal accumulation of Cu was previously reported to be associated with the development of several disease, such as wilson's disease and neuroinflammation [ 40 , 41 ]. Recently, increasing number of studies have revealed that Cu metabolic reprogramming and Cu-dependent cellular process are crucial for cancer development, and it is important to uncover the underlying regulatory mechanisms of Cu in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic diagnosis techniques and their easy accessibility raise the possibility of detecting some metabolic diseases involving Wilson’s disease (WD)[ 13 ], glycogen storage disease (GSD)[ 14 ] and α1-antitrypsin deficiency[ 15 ]. The incidence of WD is usually quoted as 1:30000, but recent genetic studies have shown a higher prevalence ranging from 1:2400 to 1:6500[ 16 ]. CLD affects approximately 1/2500 infants, and biliary atresia accounts for 1/3[ 17 ]; genetic or metabolic factors account for approximately one-third of cholestasis cases causing subsequent liver dysfunction, including citrin deficiency (CD)[ 18 ], progressive familial intrahepatic cholestasis (PFIC)[ 19 ] and Alagille syndrome (AGS)[ 20 ].…”
Section: Epidemiological Changes In Causes Of Pediatric Liver Diseasementioning
confidence: 99%
“…[3,11] Sole cynku zmniejszają wchłanianie miedzi przez układ pokarmowy oraz zwiększają jej wydalanie z kałem. [13,14] Stosowane są zarówno w początkowym okresie leczenia, jak i przewlekle w podtrzymywaniu prawidłowego stężenia miedzi w ustroju. [12] Głównym działaniem niepożądanym terapii solami cynku jest dyspepsja.…”
Section: Objawyunclassified